2010
DOI: 10.1371/journal.pone.0009628
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of Adult Male Circumcision for Prevention of Heterosexual Acquisition of HIV in Men in Sub-Saharan Africa: A Systematic Review

Abstract: BackgroundThere is conclusive evidence from observational data and three randomized controlled trials that circumcised men have a significantly lower risk of becoming infected with the human immunodeficiency virus (HIV). The aim of this study was to systematically review economic evaluations on adult male circumcision (AMC) for prevention of heterosexual acquisition of HIV in men.Methods and FindingsStudies were identified from the following bibliographic databases: MEDLINE (Ovid), EMBASE (Ovid), Cochrane Libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
1
25
0
1
Order By: Relevance
“…In a high HIV prevalence setting, each averted HIV infection would require 5 to 15 circumcision procedures (70). Furthermore, models suggest that as an HIV prevention method, MC is highly cost-effective and potentially cost saving after a period of scale-up (71; 72). While MC programs require initial expenditure for the procedure, potential adverse events, and other components of scale-up, savings are expected to accrue over time as circumcised men, their female partners, and others throughout the community avoid infection with HIV and other STIs.…”
Section: Scale-up and Potential For Large-scale Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…In a high HIV prevalence setting, each averted HIV infection would require 5 to 15 circumcision procedures (70). Furthermore, models suggest that as an HIV prevention method, MC is highly cost-effective and potentially cost saving after a period of scale-up (71; 72). While MC programs require initial expenditure for the procedure, potential adverse events, and other components of scale-up, savings are expected to accrue over time as circumcised men, their female partners, and others throughout the community avoid infection with HIV and other STIs.…”
Section: Scale-up and Potential For Large-scale Impactmentioning
confidence: 99%
“…MC scale-up to 80% coverage across priority countries in eastern and southern Africa by 2015 is associated with a net savings of $16.51 billion through averted HIV alone (71). Although estimates have varied based on the specifics of the model used and the population studied, a systematic review from 2009 found that reported cost per HIV infection averted through MC ranged from $174 to $2808 (72). These values are comparable to those for other interventions to prevent HIV, such as voluntary testing and counseling, antiretroviral therapy for prevention, and interventions to reduce mother-to-child transmission.…”
Section: Scale-up and Potential For Large-scale Impactmentioning
confidence: 99%
“…118,119 Male circumcision is an effective preventive measure to reduce susceptibility to HIV and STI transmission, and is being widely adopted in many African countries. 120,121 There is good reason for cautious optimism given all the progress which has been made in recent years on account of the tremendous efforts in public health. Since 2005, coverage of antiviral treatment in poorer countries has increased tenfold, "resulting in the fi rst decline in the number of AIDS deaths since the epidemic was recognized in the 1980s."…”
Section: Resultsmentioning
confidence: 99%
“…Several economic evaluations [11][12][13][14][15] have shown that AMC is cost effective, or even cost saving (a cost-saving intervention is one that actually saves society money in the long run by preventing costly medical care) for the prevention of heterosexual acquisition of HIV in men. A preliminary examination of the existing economic evaluations suggests that, studies have tended to focus on population in a limited geographic area, have expressed results in terms of cost per HIV infection averted (HIA), or have not considered DALYs [16]. Most of these studies did not include impact of complications association with AMC in their models [16].…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary examination of the existing economic evaluations suggests that, studies have tended to focus on population in a limited geographic area, have expressed results in terms of cost per HIV infection averted (HIA), or have not considered DALYs [16]. Most of these studies did not include impact of complications association with AMC in their models [16]. Except for Kahn et al [15], most of the authors did not consider multivariate sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%